ANTIMICROBIAL RESISTANCE PATTERNS OF ESCHERICHIA COLI O157:H7 ISOLATED FROM STOOL SAMPLE OF CHILDREN (Iraqi Journal of Medical Sciences, 2016)
Background: Enterohemorrhagic Escherichia coli is a subset of Shiga toxin-producing E. coli that can cause diarrhea or hemorrhagic colitis in humans. Hemorrhagic colitis occasionally progresses to hemolytic uremic syndrome, is a major cause ofacute renal failure in children and morbidity and mortality in adults.Objective:To determine the susceptibility and resistance of the most effective antibiotic to E.coli O157:H7 associated with bloody diarrhea.Methods:Two hundred patients with bloody diarrhea were enrolled in this study. Escherichia coli were isolated on Sorbitol MacConkey agar with Cefixime and Tellurite and tested by latex agglutination test. The susceptibility and resistance for all bacterial isolates were identified by standard procedures resistance patterns such as disk diffusion test and minimum inhibitory concentration.Results:E.coli O157:H7 found in 37 (18.5%) out of two hundred stool samples. The highest rate was found in 18 cases (48.64%) out of 37 infants aged 3-12 months, 12 cases (32.43%) in infants aged 13-24 months, and the lower rates was in children over two years old (18.9%). E.coli O157: H7 was completely resistant to gentamicin, ampicillin, nalidixic acid and co-trimoxazole; high rate of resistance to cefotaxime and ceftazidime, moderate-to-low rate of resistance to ciprofloxacin, amikacine, ceftriaxone and Imipenem and no resistances rate to levofloxacin. Out of 37 isolates 29 (78.3%) were ?-lactamase producer and 8 (21.6 %) isolates resistant to ?-lactamase antibiotic patterns but not produce ?-lactamase enzyme.Conclusion:The high-incidence rate of E. coli O157:H7 infection in children associated with limited number of drugs effective against E. coli O157:H7 with high prevalence of resistance to more than three antibiotics.Keywords:E.coli O157:H7, Enterohemorrhagic Escherichia coli, disk diffusion test, minimum inhibitory concentration.
Keywords: Ecoli O157H7; Enterohemorrhagic Escherichia coli; disk diffusion test; minimum inhibitory concentration